Identifikasi Kesiapan Lembaga dalam Penerapan Kurikulum Merdeka Belajar di PAUD Gugus II Kecamatan Pringgarata Tahun Pelajaran 2023/2024 - Nadia Fitriani; I Nyoman Suarta; Baik Nilawati Astini; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2023)
This research aims to determine the readiness of learning tools and learning supports in implementing the independent curriculum in PAUD cluster II, Pringgarata District. The type of research used is survey research. The population in this study were all PAUD institutions (KB and TK) in the Pringgarata sub-district totaling 56 institutions, while the sample in this study was 12 institutions with a sampling method using thenonprobability sampling. The data collection technique uses a questionnaire, with data analysis techniques in the form of descriptive quantitative data from the results of the questionnaire sheet. Based on the results of data analysis of the readiness of learning tools and learning supports, which consists of the availability of curriculum for implementing the Independent Curriculum (KOSP), the results were 66%, the availability of teaching modules 100%, and the availability of lesson plans 100%. Readiness to support learning in PAUD cluster II, Pringgarata sub-district already has learning support which includes the availability of school programs to improve good teacher competency with a percentage of 100%. From the results of the average percentage data above, it shows that the readiness of learning tools and learning support for implementing the independent curriculum in PAUD Cluster II, Pringgarata District, it is ready.